CYTOKINE PROFILE IN CHILDREN WITH ASTHMA, COMBINED WITH CHRONIC OPISTHORCHOSIS - L.M. Ogorodova; I.A. Deev; O.S. Fedorova; A.E. Sazonov; I.S. Popova (Union of pediatricians of Russia, 2011)
Current epidemiological studies show some correlation of prevalence and intensity of clinical manifestations of asthma, with the level of the intestinal parasites infestation in the studied population. Apparently, such a relationship of intestinal helminth invasion and allergic inflammation are formed on the basis of the «overlapping» or bipolar immunological mechanisms. In this context, there was planned and carried out the study concerning the relationship of clinical and functional parameters that characterize the intensity of inflammation in asthma and cytokine profile depending on the presence of chronic infestation Opisthorchis felineus. The study involved 212 patients (mean age 9,35 ± 0,12 years). It was established that the chronic infestation O. felineus in patients with asthma is characterized by the high levels of interleukin (IL) Th1 profile (IL 2, 10, IFN y) and low values of pro-inflammatory cytokines (IL 4, 5), which is associated with a lower degree of nonspecific airway reactivity.Key words: Opisthorchis felineus, children, cytokines, IL 4, IL 5, IL 2, IL 10, IFN y.